Effect of a Brown Rice Based Vegan Diet and Conventional Diabetic Diet on Glycemic Control of Patients with Type 2 Diabetes: A 12-Week Randomized Clinical Trial - Lee, Yu-Mi; Kim, Se-A; Lee, In-Kyu; Kim, Jung-Guk; Park, Keun-Gyu; Jeong, Ji-Yun; Jeon, Jae-Han; Shin, Ji-Yeon; Lee, Duk-Hee (PLOS ONE, 2016)
Objective Several intervention studies have suggested that vegetarian or vegan diets have clinical benefits, particularly in terms of glycemic control, in patients with type 2 diabetes (T2D); however, no randomized controlled trial has been conducted in Asians who more commonly depend on plant-based foods, as compared to Western populations. Here, we aimed to compare the effect of a vegan diet and conventional diabetic diet on glycemic control among Korean individuals. Materials and Methods Participants diagnosed with T2D were randomly assigned to follow either a vegan diet (excluding animal-based food including fish; n = 46) or a conventional diet recommended by the Korean Diabetes Association 2011 (n = 47) for 12 weeks. HbA1c levels were measured at weeks 0, 4, and 12, and the primary study endpoint was the change in HbA1c levels over 12 weeks. Results The mean HbA1c levels at weeks 0, 4, and 12 were 7.7%, 7.2%, and 7.1% in the vegan group, and 7.4%, 7.2%, and 7.2% in the conventional group, respectively. Although both groups showed significant reductions in HbA1C levels, the reductions were larger in the vegan group than in the conventional group (-0.5% vs. -0.2%; p-for-interaction = 0.017). When only considering participants with high compliance, the difference in HbA1c level reduction between the groups was found to be larger (-0.9% vs. -0.3%). The beneficial effect of vegan diets was noted even after adjusting for changes in total energy intake or waist circumference over the 12 weeks. Conclusion Both diets led to reductions in HbA1c levels; however, glycemic control was better with the vegan diet than with the conventional diet. Thus, the dietary guidelines for patients with T2D should include a vegan diet for the better management and treatment. However, further studies are needed to evaluate the long-term effects of a vegan diet, and to identify potential explanations of the underlying mechanisms. Trial Registration CRiS KCT0001771